PERANCANGAN KNOWLEDGE MANAGEMENT SYSTEM PADA KANTOR DINAS PENDIDIKAN PEMDA OGAN ILIR - Helda Yudiastuti; Irwansyah Irwansyah (Jurnal Ilmiah Matrik, 2018)
Local government education offices Ogan Ilir is the government agency that is engaged in education. Local government education offices Ogan Ilir Inventory goods are now using Information Systems, but has not used a special program to summarize all the information. Given the high level of knowledge of data loss due to mutation and retired employees, the education office there is no one system that can organize, collect, document and knowledge transfer data into information. This situation raises awareness of the importance of the application of process knowledge system (Knowledge Management Sytem). Expected to facilitate the Education Office in processing the inventory of goods, knowledge-coordinated and well-organized. Based on the description above, the authors conducted a study with the title "Designing Knowledge Management Systems In Local Government Education Office Ogan Ilir”.